1994
DOI: 10.1111/j.1365-2915.1994.tb00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and chromosomal descriptions of new species in the Anopheles subpictus complex

Abstract: Anopheles subpictus Grassi is shown to comprise four reproductively distinct species, designated A, B, C and D, occurring sympatrically in villages of Pondicherry, southeast India. Adult females were reared individually from wild larvae and examined for their morphological and chromosomal characters. Paracentric fixed inversions on the X-chromosome serve to distinguish the species cytogenetically, with no inversion heterozygotes (i.e. no interspecific hybrids) among totals of 717 species A (X+a, +b), 1863 spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 9 publications
4
76
0
1
Order By: Relevance
“…Accordingly, there were a total of 27 different types of structural aberrations out of which 12 were inversions, 8 instances of ectopically associated bands of the same or different chromosomes, 3 cases of insertional translocations, 2 asynaptic regions and 2 telomeric fusions. These types of structural changes are in conformity with the results obtained earlier by various workers about the incidence of chromosomal polymorphism in a number of species from the Oriental region (Chaudhry and Soni, 1987;Chaudhry, 1999;Suguna et al, 1994;Subbarao et al, 1994Subbarao et al, , 1999Chillar and Chaudhry, 2004;Chaudhry et al, 2005). As a consequence of the emergence of An.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Accordingly, there were a total of 27 different types of structural aberrations out of which 12 were inversions, 8 instances of ectopically associated bands of the same or different chromosomes, 3 cases of insertional translocations, 2 asynaptic regions and 2 telomeric fusions. These types of structural changes are in conformity with the results obtained earlier by various workers about the incidence of chromosomal polymorphism in a number of species from the Oriental region (Chaudhry and Soni, 1987;Chaudhry, 1999;Suguna et al, 1994;Subbarao et al, 1994Subbarao et al, , 1999Chillar and Chaudhry, 2004;Chaudhry et al, 2005). As a consequence of the emergence of An.…”
Section: Resultssupporting
confidence: 91%
“…The studies carried out so far have revealed that except for one fixed inversion in the X-chromosome which differentiates the four sibling species of An. subpictus complex, the rest fall in the category of floating inversions (Suguna, 1982;Reuben and Suguna, 1983;Suguna et al, 1994;Subbarao, 1996;Subbarao and Sharma, 1997;Chaudhry and Soni, 2000). For example, Subbarao (1998) and Subbarao and Sharma (1997) found the Oriental Anopheles subpictus to be a complex of a four reproductively isolated sibling species A, B, C and D recognized as four inversion genotypes viz: A-X a+b , B-X ab , C-X a+b and D-X +ab .…”
Section: Resultsmentioning
confidence: 99%
“…a ? b because the banding pattern of X-chromosome was found to be homologous to that reported earlier by Suguna et al (1994) for sibling species A of An. subpictus.…”
Section: Polytene Chromosome Analysissupporting
confidence: 69%
“…is a complex of four chromosomally defined sibling species, only one of which (sp. B) has been found in salt water (Suguna et al, 1994). As the specimen in this study was collected from freshwater, it is probably not this species.…”
Section: Mosquito Collections and Identificationmentioning
confidence: 68%